Seroprevalence and specificity of NMO-IgG (anti-aquaporin 4 antibodies) in patients with neuropsychiatric systemic lupus erythematosus - Závada, Jakub; Jarius, Sven (Rheumatology international, 2013)
Neuropsychiatric manifestations are present in 30-40% of patients with systemic lupus erythematosus (SLE). Recently, antibodies to aquaporin-4 (termed AQP4-Ab, or NMO-IgG), a water channel protein, were reported to be present in a subset of patients with SLE and neurological involvement. To evaluate the syndrome specificity and prevalence of serum NMO-IgG/anti-AQP4 antibodies in patients with neuropsychiatric systemic lupus erythematosus (NPSLE). Sera of 76 patients with SLE and neurological symptoms, 50 of whom met the ACR case definitions of NPSLE, were tested for AQP4-Ab in an indirect immunofluorescence assay employing HEK293 cells transfected with recombinant human AQP4. Only one of the examined sera was positive for NMO-IgG/AQP4-Ab. This patient suffered from TM, ranging over two vertebral segments on spinal MRI. None of the 75 NPSLE without TM was found to be seropositive for NMO-IgG/AQP4-Ab. NMO-IgG/AQP4-Ab in NPSLE were present only in a patient with TM and were not detectable in NPSLE patients with other neurological manifestations. Testing for NMO-IgG/AQP4-Ab positivity should be considered in patients presenting with SLE and TM. Non-longitudinally extensive lesions do no not exclude NMO-IgG/AQP4-Ab in patients presenting with SLE and TM.